Advances and challenges in the knowledge on the tropical mountain cloud forests of Mexico - Rosas Rangel, Dulce María; Mendoza, Manuel E.; Gómez-Tagle, Alberto; Tobón Marín, Conrado (Instituto de Ecología, A.C., 2019)
The "tropical mountain cloud forest" are ecosystems characterized by the level of tree strata, abundant ferns and epiphytes. Currently this type of vegetation exists in the form of relicts in some of the country's glens, so it is important to conserve this ecosystem that occupies less than 1% of the national territory and has a high value in the face of water scarcity and forests loss. Its ecological importance lies in the high diversity of flora and the presence of endemic species at threat of extinction, which have a function as a protective cover to prevent soil erosion. Its hydrological importance derives from the presence of rains and cloudiness or fog during several months through the year, which reduces solar radiation incidence by decreasing water outflow associated to evapotranspiration. It is characterized by two inputs; one is rainfall and second is horizontal precipitation, associated to fog which is intercepted by canopy. In this work, a review of the studies carried out in Mexico through specific and specialized searches in online search engines (Web of Science, ScienceResearch, Academia.edu and Google Scholar) is presented. A high number of ecological peer-reviewed research publications was found about biodiversity (fauna, floristic listings and vegetation structure), disturbance, secondary succession, ecological restoration; however, a limited number of works on ecosystem services (hydrological and carbon capture) were identified; the most recent research is related to climate change.